PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN, TINGKAT PENDIDIKAN, MASA KERJA DAN PELATIHAN TERHADAP KUALITAS LAPORAN KEUANGAN (Studi pada Satker Kanwil Kementerian Agama Propinsi Sulawesi Tengah) - Sukmawati, Andi (Katalogis, 2017)
This purpose of this study is to analyze the influence of Â understanding on government accounting standards, level education, employment, Â and training on the quality of financial statements. This study is located in the regional office of The Ministry of Religious Affairs of Centarl Sulawesi. Research Instrument is questionnaire. Sample consists of 32 administrators of budget and financial statement. Hypotheses were tested with multiple linear regression analysis with program SPSS 16.0 for Windows.The result shows that: 1) the understanding of government accounting standards have positif and significant influence on financial statements quality, 2) education level have positif and significant influence on financial statements quality, 3)employment Â t have positif and significant influence on financial statements quality, 4) training have positif and significant influence on financial statements quality. This result confirm that the understanding on government accounting standards, level of education, employment and training on the quality of financial statements.